The extensible integument of Rhipicephalus sanguineus female ticks in different feeding stages: a morphological approach - Remedio, Rafael Neodini [UNESP]; Nunes, Pablo Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2015)
Ticks are among the most important pathogen vectors worldwide, and the knowledge of their internal and external morphology may provide relevant information that will allow an adequate control of these animals. In this sense, the integument gains prominence, not only because of its wide capacity of expansion, but also due to the fact that this region is usually the first site of contact with natural and synthetic acaricides. Therefore, this study aimed to describe the morphology of alloscutal integument of R.sanguineus female ticks in three different feeding stages by means of histological and ultramorphological analysis. Significant differences were observed in all stages, with respect to the size of cells and layers, and to cuticle unfolding throughout the feeding process. Cuticle is divided into two main layers, the epicuticle and the procuticle, and is separated from a unistratified epithelium by a subcuticular layer. Procuticle, in turn, is divided into two layers, the endocuticle and exocuticle. Unfed female ticks showed cuticle with numerous folds, which decrease in quantity as the feeding expansion of the whole animal occurs. Opening of dermal glands and presence of setae also differed among groups.
Keywords: Histology; Alloscutum; Cuticle; Feeding; Brown dog tick